O poeta que pinta: um estudo dos tópoi em Manoel de Barros - Alves, Jucimara Braga (2012)
This research proposes to study the imagery topoi in the work of Manoel de Barros. In the first moment, it approaches the smallest beings, highlighting their greatness in them, set to dialogue with some concepts of Bachelard, such as resonance and repercussion, topophilia and the creative imagination. Then, it reflects on the poetic debris in Barre's work, refuse from society, as a criticism of the consumerist-capitalist society. Among these beings, it analyzes the organization of the “tin” topos and the meanings established with other images, which would make it possible for the meaning of the word to be renewed and for there to be a transformation from something unimportant to something grandiose. In this sense, this research also addresses the image of the madman, represented by the Barreano anti-heroes called ―bocós‖, ―beasts‖, ―fobos‖, demonstrating a renewed look at such beings who are also excluded from today's society; beings who dialogue with other characters in fiction and in the everyday world diagnosed as mad. Finally, it analyzes the erotic topoi, highlighting the ―slug‖ topos. In this case, the word is eroticized, when possible to establish a comparison with the sensual female body. And, in this way, the poet would also metaphorize his poetic writing.